THE EFFECT OF USING CROSSWORD PUZZLES ON INDONESIAN EFL COLLEGE STUDENTS’ VOCABULARY MASTERY - Aufa Nabila; Hafizatun Septi Arizky; Novelia Fitriani; M. Aripin Ilham; Muhammad Hakim; Abdul Syahid (STRATEGY : Jurnal Inovasi Strategi dan Model Pembelajaran, 2026)
ABSTRACT This study investigates the effect of using crossword puzzles on Indonesian EFL college students’ vocabulary mastery. Vocabulary is an important aspect of learning English because it helps students understand and express meaning effectively. There's so many EFL learners are still struggle to remember vocabulary, spell words correctly, and use them appropriately in different contexts. For this reason, more engaging learning activities are needed to support vocabulary development. This study employed a pre-experimental design using a one-group pre-test and post-test approach to investigate the effect of crossword puzzle activities on students' vocabulary mastery. The study involved 27 fourth-semester students of the English Education (Tadris Bahasa Inggris) Study Program selected through purposive sampling. The data were collected through vocabulary tests administered before and after the implementation of crossword puzzle activities. The results indicated an improvement in students’ vocabulary mastery, with the mean score increasing from 93.34 in the pre-test to 97.26 in the post-test. A paired-samples t-test revealed a statistically significant difference between the pre-test and post-test scores (p < 0.001), with a large effect size (Cohen’s d = 0.91). These findings suggest that crossword puzzles are effective in enhancing students’ vocabulary mastery. These findings indicate that crossword puzzles can encourage active participation, provide repeated exposure to vocabulary, and create more meaningful learning experiences. Therefore, crossword puzzles may be considered an effective and enjoyable alternative strategy for teaching vocabulary in EFL classrooms. ABSTRAK Penelitian ini mengkaji pengaruh penggunaan teka-teki silang terhadap penguasaan kosakata mahasiswa program Bahasa Inggris sebagai Bahasa Asing (EFL) di perguruan tinggi. Kosakata merupakan aspek penting dalam pembelajaran Bahasa Inggris karena membantu mahasiswa memahami dan mengekspresikan makna secara efektif. Banyak pelajar bahasa Inggris sebagai bahasa asing (EFL) yang masih kesulitan mengingat kosakata, mengeja kata dengan benar, dan menggunakannya secara tepat dalam konteks yang berbeda. Oleh karena itu, diperlukan kegiatan pembelajaran yang lebih menarik untuk mendukung pengembangan kosakata. Penelitian ini menggunakan desain pra-eksperimen (pre-experimental design) dengan rancangan one-group pre-test–post-test untuk mengetahui pengaruh penggunaan aktivitas crossword puzzle terhadap penguasaan kosakata mahasiswa. Penelitian melibatkan 27 mahasiswa semester IV Program Studi Tadris Bahasa Inggris yang dipilih dengan teknik purposive sampling.. Hasil penelitian menunjukkan bahwa nilai rata-rata kosakata meningkat dari 93,34 pada pra-tes menjadi 97,26 pada pasca-tes. Uji-t sampel berpasangan menunjukkan perbedaan yang signifikan antara skor pra-tes dan pasca-tes (p < 0,001), dengan ukuran efek yang besar (Cohen’s d = 0,91). Temuan ini menunjukkan bahwa teka-teki silang efektif dalam meningkatkan penguasaan kosakata mahasiswa. Temuan ini menunjukkan bahwa teka-teki silang dapat mendorong partisipasi aktif, memberikan paparan berulang terhadap kosakata, dan menciptakan pengalaman belajar yang lebih bermakna. Oleh karena itu, teka-teki silang dapat dianggap sebagai strategi alternatif yang efektif dan menyenangkan untuk mengajarkan kosakata di kelas EFL.